Método rápido para a determinação simultânea de resíduos de agrotóxicos e medicamentos veterinários em alimentos de origem animal por LC-MS/MS - Prestes, Osmar Damian (2011)
Currently, one of highest trade barriers that Brazil has found for the marketing of their products from the agribusiness chain is the lack of informations on the presence of residues in foods produced in the country. Due to the complexity of the matrices of animal origin and the low concentrations of pesticides and veterinary drugs present, there is a great need to develop efficient and reliable analytical methods for identification and quantification of residues. In this study we evaluated the linearity range of standard curves (eight concentration levels and six injections each), limit of detection (LOD), limit of quantification (LOQ), matrix effect and the precision and accuracy, in terms of percent recovery for 91 pesticides and 9 veterinary drugs analyzed and validated by the QuEChERS method and Liquid Chromatography coupled with Tandem Mass Spectrometry in meat, liver, kidney, milk and egg samples. For this, we performed the fortification of previously homogenised samples with solutions containing 100 compounds in three fortification levels (10, 25 and 50 μg kg-1), 6 replicates for each level, and applied the method extraction. The modified QuEChERS extraction method consist weighing 10 g of the matrix (10 mL for milk), 10 mL of acetonitrile containing 1% of acetic acid (v/v) and shake handly and vigorously for about 1 min. After, 4 g of anhydrous magnesium sulfate and 1.7 g anhydrous sodium acetate, repeating the agitation. After centrifugation for 8 min (3500 rpm), 4 mL of extract were transferred to another tube containing 600 mg of anhydrous magnesium sulfate and 500 mg C18, repeating the agitation and centrifugation. The extract was diluted (1:1) in the mobile phase, and then analyzed by LC-MS/MS. Analytical curves prepared in solvent and in all matrix extracts, showed adequate linearity between 1.0 and 250.0 μg L-1, with determination coefficients greater than 0.995. The method showed satisfactory recovery values between 70 and 120% (RSD ≤ 20%) to about 85% of the compounds in all matrices at levels 10, 25 and 50 μg kg-1 (for milk μg L-1). In general, the method presented LOQm value of 10 g kg-1 (μg L-1). Therefore, we concluded that the proposed method can be applied efficiently for the determination of pesticide and veterinary drugs residues in the different evaluated matrices without any modification of the method.